Herpetic Esophagitis in Immunocompetent Medical Student - Andréia Vidica Marinho; Vinícius Mendes Bonfim; Luciana Rodrigues de Alencar; Sebastião Alves Pinto; João Alves de Araújo Filho (Case Reports in Infectious Diseases)
Esophagitis caused by herpes simplex virus (HSV) is often documented during periods of immunosuppression in patients infected with human immunodeficiency virus (HIV); it is rare in immunocompetent diagnosed patients. Case reports of herpetic esophagitis in students of health sciences are extremely rare. The disease presents with a clinical picture characterized by acute odynophagia and retrosternal pain without obvious causes and ulcers, evidenced endoscopically in the middistal esophagus. Diagnosis depends on endoscopy, biopsies for pathology studies, and immunohistochemistry techniques. The disease course is often benign; however, treatment with acyclovir speeds the disappearance of symptoms and limits the severity of infection. In this report, we present a case of herpetic esophagitis in an immunocompetent medical student, with reference to its clinical features, diagnosis, and treatment. The disease may have manifested as a result of emotional stress experienced by the patient.